ERRATUM TO: IMPLEMENTATION OF INTERNET-BASED EMERGENCY MEDICAL SERVICE: A SOLUTION TO IMPROVE RESPONSE TIME IN OUT-OF-HOSPITAL CARDIAC ARREST AND ITS POTENTIAL APPLICATION IN INDONESIA - Ismail Fahmi; Elly Nurachmah (Belitung Raya Foundation, Indonesia, 2020)
After the publication of the article (Fahmi & Nurachmah, 2018), it has been brought to our attention that the wrong title was used on the initial publication. The correct title of this article is “Implementation of Internet-based emergency medical service: A solution to improve response time in out-of-hospital cardiac arrest and its potential application in Indonesia.” The original version of the article has been updated to reflect this. The reference format in this article has also been updated. The publisher apologizes for the errors. The corrected article can be seen in the following link: https://doi.org/10.33546/bnj.573